PEMBERDAYAAN MASYARAKAT DESA MEKAR SARI DALAM PENINGKATAN PENGETAHUAN PERTANIAN, PERKAWINAN ANAK, PENGELOLAAN LINGKUNGAN, DAN INFRASTRUKTUR - Tripena, Dea; Salsabela, Cahya; Marbun, Julianti; Debora, Helse; Putra Air langga, Iqbal (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
This article discusses the implementation of the Community Service Program (KKN) carried out by students of Universitas Panca Bakti in Mekar Sari Village over a period of 30 days in August 2025. The main objective of this activity was to empower the local community through education in the areas of agriculture, child protection, environmental management, and rural infrastructure development. In the agricultural sector, awareness campaigns were conducted on the importance of commodity data collection and production volume. Field visits were carried out to identify challenges faced by farmers, such as the limited use of agricultural technology. Proposed solutions included training in the use of organic fertilizers and drip irrigation systems. To address the high rate of child marriage in the village, educational sessions were held regarding the Child Protection Law and the crucial role of parents in supervision and character education. In terms of environmental issues, low public awareness led to the initiation of community clean-up programs and training on waste management. Infrastructure development funded through the Village Fund was also encouraged to improve residents' quality of life. Furthermore, education was provided on the negative impacts of juvenile delinquency, including drug abuse and fighting. Overall, the KKN program had a positive impact, although challenges remain, such as limited agricultural technology, low environmental awareness, and a high rate of child marriage. Recommendations for the village government include strengthening agricultural outreach programs, integrating environmental initiatives, and supporting children's education. The report also recommends that parents, schools, and village authorities continue and expand the implemented programs to ensure sustainable village development.